Assessment of Gross Parameters in Maternal Albino Rats after Consumption of a High Carbohydrate Diet: A Comparative Study (Medical Forum Monthly, 2023)
Objective: Assessment of gross parameters of abdominal circumference and maternal weight in maternal albino rats after utilization of a high carbohydrate diet.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Anatomy Department of Al-Tibri Medical College and Hospital from June 2022 to December 2022.Materials and Methods: After attaining ethical approval from the review board, 8 female albino rats were randomly sampled and allocated into two groups with 2 male rats also being introduced into the two groups for mating purposes. The allocation in the groups was such that in Group A the rats received a normal diet, while in Group B they received a high carbohydrate diet through the gestational period. The weights of the rats and the abdominal circumference were measured after they achieved pregnancy on the 1st and 21st day, in the form of mean and standard deviation. Data were analyzed using SPSS version 21.0, with a comparison between groups done using an independent t-test, while a simple t-test was used for comparison within groups.Results: No significant difference is observed between Group A and B in maternal weight on the 1st day (P: 0.760) or the 21st day (P: 0.986) of pregnancy. No significant difference is observed between Group A and B in abdominal circumference on the 1st day or the 21st day of pregnancy. A significant difference is observed within Group A when comparing the abdominal weight on the 1st and 21st day of pregnancy (P: ). A significant difference is observed within Group B when comparing the abdominal weight on the 1st and 21st day of pregnancy (P: ).Conclusion: High carbohydrate diet has no significant effect on both abdominal circumference and maternal weight when compared to a normal diet.